HEMS: Automated Online System for SEGAK Analysis and Reporting - Engku Fadzli Hasan, Syed Abdullah; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Amran, Ahmed (2016)
The Ministry of Education Malaysia (MOE) implemented the National Physical Fitness Standard (SEGAK) for Malaysian School Children Assessment Program. Ever since, the SEGAK assessment data had been collected by the respective teachers in every school twice a year, then its summary is being submitted to the State Department of Education manually through email. This creates problems such as lack of a standardized report format, complex formula in calculating SEGAK score and different data interpretation. In this paper, an integrated and automated SEGAK submission and analysis system is proposed. The system, which is known as Health Monitoring System (HEMS), is a web based system developed with an automated pre-processing method and implemented three tier architecture. HEMS have a centralized database that collects the assessment data from seven districts in Terengganu. A total of 35,681 data was collected from 213 primary schools, and 27,201 data from 44 secondary schools, giving a big total of 67,519 data. During the pre-processing, 4,637 data or 6.9% of the collected data were excluded due to wrong and incomplete information. Using HEMS template, the submitted data have a consistent format of data types. HEMS generates an automated analysis and reporting for the use of related authorities.